Money, politics and religion: a survey of Anglo-American influence in TESOL - Gregory Hadley (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2004)
This paper will consider some of the aspects related to the teaching of English as an International Language. What are some of the wider sociopolitical forces that shape our decisions as language teachers? As educators ethically reflect upon their role, how will their decisions support or subvert the aims of those who have a stake in the continued supremacy of the English language?